How many years of monitoring are needed to determine plantation success in the context of restoration?: Overview in relation to microsites and seed provenance - Simoes Macayo, Nayara; Renison, Daniel (Bosque (Valdivia), 2017)
Field studies on the success of reforestation mostly report monitoring periods ranging from months to years, assuming that these periods are representative of the performance of individuals over longer time periods. We test this assumption by monitoring, for 15 years, a plantation of 585 trees of Polylepis australis produced from two seed provenances and planted in three types of microsites in the Mountains of Córdoba, Argentina. We monitored at year 0 (when planted), and years 1, 2, 3, 4, 5, 6, 10, 12 and 15 to evaluate whether the combined effects of the treatments on survival and height had similar patterns throughout time. We further determined if height in the different years of monitoring was a good indicator of the results of the last measurement year, the probability that the trees produce seeds at year 12, and the number, weight and viability of seeds produced. The difference in the height of the seedlings between the two provenances was significant since year 0, while among microsites it became significant from year 3 onwards. Height was an unbiased indicator of all reproductive traits when measured from year 2 onwards. Finally, mortality was not affected by the treatments and reached a relatively constant rate from year 4 onwards. This study provides evidence that short-term evaluations (e.g., 2 years) may be representative of future behavior of the monitored individuals.